PERSEPSI PENGGUNA JASA PENYEBERANGAN BAKAUHENI-MERAK TERKAIT INOVASI PEMBELIAN TIKET MELALUI APLIKASI FERIZY - Gesta Rallimo Pratiasa; Budhi Waskito; M. Denu Proyo (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2025)
This research aims to explore and analyze public perceptions of the use of ferry ticket booking applications from Bakauheni Port to Merak Port. This study aims to determine the extent to which the innovation of the ferizy application is useful and helps some people in ordering ferry tickets online. Identifying the main obstacles and difficulties in ordering Ferizy applications, including the existence of ticket brokers. This study will use qualitative research methods, which include data collection techniques, such as surveys, interviews, or secondary data analysis. This approach was chosen to ensure that the data obtained is comprehensive and representative. The results of the study show that: The perception of Bakauheni-Merak ferry service users towards the Ferizy application varies, namely users feel the benefits of increased efficiency, comfort, and reduced queues. Factors that influence user perceptions in using the Ferizy application include performance expectations (application benefits), ease of use (user-friendliness), social influence, and facility conditions. The efforts of PT ASDP Bakauheni branch to increase the positive perception of Bakauheni-Merak ferry service users regarding ticket purchase innovations through the application aim to reduce congestion, queues at ports, and scalping practices, as well as provide a smoother and more comfortable experience for service users on the Merak-Bakauheni route.